Mathematical mindsets : unleashing students' potential through creative math, inspiring messages and innovative teaching - Boaler, Jo, 1964-; Dweck, Carol S., 1946- (San Francisco, CA : Jossey-Bass; a Wiley Brand, 2016)
"Mathematical Mindsets provides practical strategies and activities to help teachers and parents show all children, even those who are convinced that they are bad at math, that they can enjoy and succeed in math. Jo Boaler--Stanford researcher, professor of math education, and expert on math learning--has studied why students don't like math and often fail in math classes. She's followed thousands of students through middle and high schools to study how they learn and to find the most effective ways to unleash the math potential in all students. There is a clear gap between what research has shown to work in teaching math and what happens in schools and at home. This book bridges that gap by turning research findings into practical activities and advice. Boaler translates Carol Dweck's concept of 'mindset' into math teaching and parenting strategies, showing how students can go from self-doubt to strong self-confidence, which is so important to math learning. Boaler reveals the steps that must be taken by schools and parents to improve math education for all"--Publisher's website.
The brain and mathematics learning -- The power of mistakes and struggle -- The creativity and beauty in mathematics -- Creating mathematical mindsets: the importance of flexibility with numbers -- Rich mathematical tasks -- Mathematics and the path to equity -- From tracking to growth mindset grouping -- Assessment for a growth mindset -- Teaching mathematics for a growth mindset.
"A Wiley brand."
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Middle school); Mathematics -- Study and teaching (Secondary); Mathematics -- Study and teaching (Secondary.)